Heteranthera yucatana (Pontederiaceae), a new, threatened species from the Mexican Yucatan Peninsula - Carnevali, Germán; Duno De Stefano, Rodrigo; Ramírez-Morillo, Ivón M.; Grande Allende, José R.; Barrios, Yeni; Tapia-Muñoz, José Luis (Phytotaxa, 2022)
A new species of Heteranthera (Pontederiaceae), H. yucatana, is described, discussed, and iconographically documented based on material from Yucatan state, Mexico. The species is known from a few small ponds along a narrow strip of dry forests and shrublands over limestone outcrops and derived soils along the northwestern edge of the Yucatan Peninsula. The new species is related and has been hitherto confused with H. seubertiana from eastern Brazil but is easily distinguishable by its substantially smaller habit and flowers. Furthermore, the perianth lobes are lilac with a white-greenish basal blotch with yellowish towards the apex (as opposed to yellow lobes with proximal brownish spots). Also, the two lateral filaments are conspicuously inflated obliquely, as in Heteranthera mexicana, from which it differs by its much smaller vegetative size and some floral characters. The conservation status of the new species is assessed as Endangered according to the IUCN criteria. The genus Heteranthera consists of three species in the Yucatan Peninsula: H. dubia, H. limosa, and H. yucatana. Distributional maps for all Heteranthera from the area covered are presented. Finally, we offer a key to Heteranthera of the area.